Getting involved in clinical trials research in the UK: how can Clinical Research Networks help?. Issue 2 (10th January 2012) - Hull, Mark A; Yiannakou, Yan; Gower, Jonathan; Ryder, Stephen D; Bloom, Stuart L; Rees, Colin R
Abstract : The Clinical Research Networks of the National Institute of Health Research have transformed clinical research in the UK, leading to a doubling in the number of patients involved in clinical research studies over the past 3 years. This has been achieved by streamlining the trials approvals process, by providing local infrastructure such as research nurse support for clinical trials recruitment and through recognition of the time and funding necessary for clinicians to contribute to clinical research. Here, we describe the structure and roles of the Comprehensive Clinical Research Networks in gastrointestinal disease and hepatology, particularly in England. We will explain how the networks have already accelerated clinical research in gastrointestinal and liver disease, as well as provide a simple guide about how individual clinicians can contribute to ongoing studies via the networks.